2016
DOI: 10.1109/lmwc.2016.2614970
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Subwavelength Radial Grooves to Support Spoof Surface-Plasmon-Polariton Waves

Abstract: This letter introduces radial grooves as a feasible geometry to support spoof surface-plasmon-polariton (SPP) waves propagating along a vacuum-metallic interface. Through the analytical derivation of a dispersion relation, validated also with full-wave simulations, the ability of radial grooves to operate in the fundamental mode at the microwave regime is demonstrated. Also, results demonstrate the utility of radial geometries to decrease the depth of the grooves, in comparison with the widely used rectangular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It is observed that all the grating structures are capable of confining electromagnetic waves on their surfaces with the increase in depth of groove, and the cutoff frequency clearly depends on the groove depth. Nevertheless, it is indicated that proposed structure attains lowest cutoff frequency as its deviation from the light line is highest, proving its stronger ability of confining surface wave as compared to conventional rectangular grooves . The key reason is the realization of gradual cutoff mode for proposed geometry (analogous to annular sector waveguides) showing greater attenuation of wave in contrast to rectangular groove …”
Section: Dispersion Characteristics Of Proposed Ct Groove Structurementioning
confidence: 93%
See 4 more Smart Citations
“…It is observed that all the grating structures are capable of confining electromagnetic waves on their surfaces with the increase in depth of groove, and the cutoff frequency clearly depends on the groove depth. Nevertheless, it is indicated that proposed structure attains lowest cutoff frequency as its deviation from the light line is highest, proving its stronger ability of confining surface wave as compared to conventional rectangular grooves . The key reason is the realization of gradual cutoff mode for proposed geometry (analogous to annular sector waveguides) showing greater attenuation of wave in contrast to rectangular groove …”
Section: Dispersion Characteristics Of Proposed Ct Groove Structurementioning
confidence: 93%
“…It can be noticed from Figures C and A that same lower level of cutoff frequency can be achieved by proposed CT SSPP with a shallower groove (6 mm) in contrast to deeper rectangular groove (11.4 mm) structure. This is the desired property of the SSPP in general, to preserve the original boundary which can be achieved by the shallow grooves . The benefit of compact plasmonic structure can be obtained by designing shallow gratings.…”
Section: Dispersion Characteristics Of Proposed Ct Groove Structurementioning
confidence: 99%
See 3 more Smart Citations